Outsourcing von Instandhaltungsleistungen, untersucht am Beispiel der Automobilindustrie - Jürgen Kroha (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 1996)
For years the German automobile industry has been facing a growing competition from Japan as well as from the emerging markets. Increasing tendencies towards globalization, an even faster change in customer needs and a stronger contraction of the product life cycle necessitate new flexible production methods and management concepts to maintain or to restore competitiveness. As possible means to achieve this, slogans like Lean Production, downsizing and outsourcing are mentioned. One area in which unused producticity potential is assumed to exist is maintenance. New maintenance concepts, first of all Total Productive Maintenance (TPM), are expected to reduce the maintenance costs, to increase the plant availability and to make a coordinate interaction between maintenance and production possible. Within this context the advantages and disadvantages of the outsourcing of maintenance services are being discussed. In order to fill the theoretical framework some interviews were carried out with members of management and chiefs of maintenance from companies of the automobile industry. The intention was to gain information about the actual situation of the plant maintenance, used methods and criterias for decisions concerning outsourcing and the future potential for outside maintenance services. This paper will give a summary of the most important results of this inquiry
Keywords: 330